The Crassispora kosankei-Cystoptychus azcuyi palynozone of the Upper Carboniferous Tupambi Formation, Tarija Basin, northern Argentina - Di Pasquo Lartigue, Maria (2002)
Well-preserved and diverse palynomorph assemblages were recovered from surface and core samples from the middle to upper section of the Tupambi Formation. The latter is the basal unit of the Machareti Group (Upper Carboniferous) of the Tarija Basin, northern Argentina. Assemblages are composed of trilete miospores, one hilate species, monosaccate pollen grains (one species striated), one praecolpate species and green algae (Botryococcus). Two key species are Cystoptychus azcuyi sp. nov. and Crassispora kosankei (Potonié and Kremp) Bharadwaj emend. Smith and Butterworth enable definition of the first palynozone for this basin. The age, as well as the biostratigraphic and paleogeographic significance of the palynoflora is discussed.